2003
DOI: 10.1046/j.1365-2222.2003.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal fish oil supplementation in pregnancy reduces interleukin‐13 levels in cord blood of infants at high risk of atopy

Abstract: This study provides preliminary evidence that increasing neonatal n-3 PUFA levels with maternal dietary supplementation can achieve subtle modification of neonatal cytokine levels. Further assessment of immune function and clinical follow-up of these infants will help determine if there are any significant effects on postnatal immune development and expression of allergic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
158
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(177 citation statements)
references
References 48 publications
(57 reference statements)
7
158
1
3
Order By: Relevance
“…Dunstan et al (26) found a consistent trend for attenuated infant Th1 (IFN␥), Th2 (IL-5, IL-13) as well as IL-10 responses to allergens after -3 supplementation of 89 atopic mothers during pregnancy. However, the neonates, whose mothers received fish oil, had significantly lower levels of circulating IL-13 in cord blood compared with the control group, which may reflect a subtle cytokine-shift favoring Th1 immunity (27). On the other hand, we did not see any effect of maternal -3 LCPUFA supplementation on chemokines when analyzing all infants, although high EPA and DHA concentrations very early in life were associated with high levels of the Th1 chemokine CXCL11 in the infant.…”
Section: Discussionmentioning
confidence: 90%
“…Dunstan et al (26) found a consistent trend for attenuated infant Th1 (IFN␥), Th2 (IL-5, IL-13) as well as IL-10 responses to allergens after -3 supplementation of 89 atopic mothers during pregnancy. However, the neonates, whose mothers received fish oil, had significantly lower levels of circulating IL-13 in cord blood compared with the control group, which may reflect a subtle cytokine-shift favoring Th1 immunity (27). On the other hand, we did not see any effect of maternal -3 LCPUFA supplementation on chemokines when analyzing all infants, although high EPA and DHA concentrations very early in life were associated with high levels of the Th1 chemokine CXCL11 in the infant.…”
Section: Discussionmentioning
confidence: 90%
“…These observations suggest that LC n-3 PUFA during pregnancy do have effects on neonatal immune function. Furthermore, infants in the fish oil group were consistently less likely to develop clinical features including food allergy, recurrent wheeze, persistent cough, diagnosed asthma, angioedema, or anaphylaxis, compared with the control group (Dunstan et al 2003b). Although there was no difference in the frequency of atopic dermatitis at 1 year of age, infants in the fish oil group had significantly less severe disease (P ¼ 0·045), and were three times less likely to have a positive skin prick test to egg allergen at 1 year of age (P ¼ 0·055).…”
Section: Modulating Immune and Inflammatory Activity With Dietary N-3mentioning
confidence: 93%
“…Epidemiological studies conducted in children revealed an inverse association between high fish consumption, which provides long chain omega-3 fatty acids, and the prevalence of asthma and bronchial hyperresponsiveness, and inferred that a decreased omega-6 to omega-3 ratio attenuates the inflammatory immune reaction [8][9][10][11]. Evidence from a recent clinical study in neonates indicates that altered membrane PUFA profiles during gestation may influence immunological function [12].…”
mentioning
confidence: 99%